The New Keynesian Model and the Long-run Vertical Phillips Curve: Does it hold for Germany? - Ulrich Fritsche; Jan Gottschalk (Hamburg University, Department Economics and Politics, 2006)
New-Keynesian macroeconomic models typically assume that any long-run trade-off between inflation and unemployment is ruled out. While this appears to be a reasonable characterization of the US economy, it is less clear that the natural rate hypothesis necessarily holds in a European country like Germany where hysteretic effects may invalidate it. Inspired by the framework developed by Farmer (2000) and Beyer and Farmer (2002), we investigate the long-run relationships between the interest rate, unemployment and inflation in West Germany from the early 1960s up to 2004 using a multivariate co-integration analysis technique. The results point to a structural break in the late 1970s. In the later time period we find for west Germany data a strong negative correlation between the trend components of inflation and unemployment. We show that this finding contradicts the natural rate hypothesis, introduce a version of the New Keynesian model which allows for some hysteresis and compare the effectiveness of monetary policy in these two models. In general, a policy rule with an aggressive response to a rise in unemployment performs better in a model with hysteretic characteristics than in a model without.
Keywords: B22; C32; E24; 330; Cointegration; Vector error Correction Model; Unemployment; Phillips Curve; Hysteresis